The role of institutional isomorphism in explaining the voluntary IFRS adoption - Begoña GIner; Paloma Merello; Miho Nakamura; Francisca Pardo (Revista de Contabilidad: Spanish Accounting Review)
Since 2005, International Financial Reporting Standards (IFRS) have been widely used on a mandatory basis worldwide, but some countries are relevant exceptions to this policy. Based on the institutional isomorphism framework, this study examines the reasons why listed companies voluntarily adopt IFRS in a very specific environment: Japan. Using financial and non-financial data, we conduct a comprehensive investigation of the determinants of IFRS adoption. We use a multi-period logit model that takes into account all annual decisions made during the period 2013-2018. We confirm that both coercive and normative isomorphism associated with some legislative changes, together with mimetic isomorphism embedded in Japanese culture, lead firms to adopt IFRS rather than Japanese General Accepted Accounting Principles (J-GAAP). These findings suggest that the legitimacy of IFRS makes this set of standards a more appropriate reporting system to deal with the uncertainty associated with the country's openness to the outside world.